Nigeria [In West African agriculture and climate change: A comprehensive analysis] - Hassan, Shuaib M.; Kuenobe, Celestine E.; Jalloh, Abdulai; Nelson, Gerald C.; Thomas, Timothy S. (International Food Policy Research Institute, 2013)
Our purpose in this chapter is to help policymakers and researchers better understand and anticipate the likely impacts of climate change on agriculture and on vulnerable households in Nigeria. We do this by reviewing current data on agriculture and economic development, modeling anticipated changes in climate between now and 2050, using crop models to assess the impact of climate change on agricultural production, and globally modeling supply and demand for food to predict food price trends.